An investigation on the behavior of stiffened coupled shear walls considering axial force effect. (16th February 2012) - Hadidi, Ali; Farahmand Azar, Bahman; Khosravi, Hossein
SUMMARY: In most of tall buildings, the main contribution of lateral loads is carried by coupled shear walls. In some cases, the necessary stiffness to withstand the lateral load may not be afforded due to low depth of connecting beams. In order to increase the capacity of the coupled shear walls, beams with high stiffness are added to the system at particular levels. Hence, stiffened coupled shear walls (SCSW) will be produced. Such walls are under axial load resulting from their weight, and this axial load affects the behavior of walls because of their excessive height. In this paper, a new method considering the effect of axial force for geometrically nonlinear analysis of the SCSW has been presented. A computer program has been developed inmatlab, and numerical examples have been solved to demonstrate the reliability of this method. The results of the examples show the agreement between the present method and the other methods given in the literature. The effects of the various positions and rigidities of the stiffening beam on the internal forces and the lateral deflection of the structure considering axial force effect have also been investigated. Copyright © 2012 John Wiley & Sons, Ltd.